Inisiasi Kebun Buah Masyarakat untuk Mendukung Ketahanan Pangan dan Penghijauan di Desa Taringen Kabupaten Gunung Mas Provinsi Kalimantan Tengah - Made Dirgantara; Suzet Rotua Tasya Nababan; Rahmat Manalu; Shelvina Shelvina; Tessalonika Tessalonika; Dobra Agustobelo; Windi Freza; Widya Kharisma F (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
The lack of plantation and agricultural products in the form of fruits and vegetables resulted in the scarcity and high price of these commodities in Taringen Village, which became a food security problem in this village. Thus, this has become one of the focuses of the main work program of implementing the Independent Thematic Real Work Lecture at the University of Palangka Raya in Taringen Village. One of the work programs implemented to overcome the problem of food security namely the initiation of fruit gardens for the Taringen Village community. In addition to food security, the initiation of the target village fruit garden also has a reforestation function because the planting area is a strategic location. After all, it is located around the market and the asphalt manufacturing plant of PT. Kalidra so that later it can reduce air pollution due to smoke generated from the asphalt production process at the factory. Site evaluations, site preparation, the creation of necessary organic fertilizers, the planting and upkeep of fruit trees, and instruction in the creation of necessary organic fertilizers (compost) are the techniques employed. The findings revealed that after 22 days of planting, 63 crystal guava trees (Psidium guajava L.) had grown satisfactorily and reached an average height of 25.33 cm. Due to its numerous advantages, the guava variety (Psidium Guajava L) is presently quite well-liked in Indonesia. In Taringen Village, Gunung Mas Regency, Central Kalimantan Province, community fruit gardens were successfully launched with the help of the locals and government. The Multipurpose Business-Cooperative Balawan Hapakat served as the activity partner after students and the local community completed the first upkeep of the orchard.